Effects of PPARγ Agonist Pioglitazone on Redox-Sensitive Cellular Signaling in Young Spontaneously Hypertensive Rats. (18th December 2013) - Dovinová, Ima; Barancik, Miroslav; Majzunova, Miroslava; Zorad, Stefan; Gajdosechová, Lucia; Gresová, Linda; Cacanyiova, Sona; Kristek, Frantisek; Balis, Peter; Chan, Julie Y. H.
Abstract : PPAR γ receptor plays an important role in oxidative stress response. Its agonists can influence vascular contractility in experimental hypertension. Our study was focused on the effects of a PPAR γ agonist pioglitazone (PIO) on blood pressure regulation, vasoactivity of vessels, and redox-sensitive signaling at the central (brainstem, BS) and peripheral (left ventricle, LV) levels in young prehypertensive rats. 5-week-old SHR were treated either with PIO (10 mg/kg/day, 2 weeks) or with saline using gastric gavage. Administration of PIO significantly slowed down blood pressure increase and improved lipid profile and aortic relaxation after insulin stimulation. A significant increase in PPAR γ expression was found only in BS, not in LV. PIO treatment did not influence NOS changes, but had tissue-dependent effect on SOD regulation and increased SOD activity, observed in LV. The treatment with PIO differentially affected also the levels of other intracellular signaling components: Akt kinase increased in the the BS, while β -catenin level was down-regulated in the BS and up-regulated in the LV. We found that the lowering of blood pressure in young SHR can be connected with insulin sensitivity of vessels and that β -catenin and SOD levels are important agents mediating PIO effects in the BS and LV.